2023
DOI: 10.1021/jacs.2c09874
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Coupling of Nitric Oxide by Cu(I): Stepwise Formation of Mono- and Dinitrosyl Species En Route to a Cupric Hyponitrite Intermediate

Abstract: Transition-metal-mediated reductive coupling of nitric oxide (NO (g) ) to nitrous oxide (N 2 O (g) ) has significance across the fields of industrial chemistry, biochemistry, medicine, and environmental health. Herein, we elucidate a density functional theory (DFT)-supplemented mechanism of NO (g) reductive coupling at a copper-ion center, [(tmpa)Cu I (MeCN)] + (1) {tmpa = tris(2pyridylmethyl)amine}. At −110 °C in EtOH (<−90 °C in MeOH), exposing)] 2+ (OO Xray ) complex. Complementary stopped-flow kinetic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 115 publications
0
9
0
Order By: Relevance
“…The slope of the double-logarithmic plot is 0.71 for both high and low nitrite concentrations, which is indicative of a side reaction that only affects the catalyst concentration (see Figure S4). Previously, nonelectrochemical studies on Cu I (tmpa) have shown that Cu(I) dimers can form in solution both in the absence , and presence of NO . Hence, we assume that similar Cu(I) dimeric species form upon reduction of the catalyst under our electrochemical conditions, resulting in an effective lower catalyst concentration.…”
Section: Results and Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The slope of the double-logarithmic plot is 0.71 for both high and low nitrite concentrations, which is indicative of a side reaction that only affects the catalyst concentration (see Figure S4). Previously, nonelectrochemical studies on Cu I (tmpa) have shown that Cu(I) dimers can form in solution both in the absence , and presence of NO . Hence, we assume that similar Cu(I) dimeric species form upon reduction of the catalyst under our electrochemical conditions, resulting in an effective lower catalyst concentration.…”
Section: Results and Discussionmentioning
confidence: 92%
“…For determination of the reaction order, we rationalized that Cu(tmpa) selectively catalyzes the one-electron reduction of nitrite. It is known that Cu I (tmpa) is also able to produce N 2 O during the reduction of nitrite, , due to the disproportionation of the generated NO to N 2 O in protic solvents. , However, this side reaction does not lead to the consumption of extra electrons and is suppressed in the presence of high concentrations of NO 2 – and low concentrations of NO, as binding of NO to Cu(tmpa) is only weak. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations